Aramid fiber-based heating paper and preparation method thereof
By using nanofiber dispersion liquid and meta-aramidated fibers in the preparation of carbon fiber heating paper, the problems of uneven dispersion of carbon fiber and insufficient high-temperature heating performance were solved, and aramid-based heating paper with high uniformity, excellent mechanical properties and high heat efficiency were prepared.
Patent Information
- Application Number
- CN202411919351.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing carbon fiber heating paper is prone to agglomeration and agglomeration during the dispersion process, resulting in uneven dispersion, uneven temperature distribution, safety hazards, and the prior art is difficult to meet the needs of the field of high-temperature heating.
The carbon fiber and aramid chopped fibers were dispersed and precipitated by nanofiber dispersion. Meta-aramid precipitated fibers were obtained by high-speed shearing and multi-stage water washing. Then, aramid-based heating paper was prepared by wet molding, pressing, drying and hot pressing.
It achieves uniform dispersion of carbon fiber, improves the uniformity and mechanical properties of aramid-based heating paper, has higher heating efficiency and better temperature resistance, and is suitable for high-temperature heating fields.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to aramid-based heating paper and a preparation method thereof, belonging to the technical field of synthetic fiber paper manufacturing. Background Art
[0002] Carbon fiber is an inert fiber material with high tensile strength, light weight, high temperature resistance, good conductivity and corrosion resistance. Its carbon content is higher than 95%, and the graphite layer on the surface is tightly and orderly arranged, resulting in a smooth surface of the carbon fiber and no functional groups. At present, the production and processing of carbon paper mainly rely on wet forming, that is, dispersing carbon fiber in an aqueous dispersant, and then preparing carbon paper through chemical compounding and high temperature treatment. In the process of dispersing carbon fiber, carbon fiber is very easy to aggregate and agglomerate, resulting in uneven dispersion. As a result, the prepared carbon fiber heating paper will have a uniform temperature distribution, and local overheating will also cause huge safety hazards.
[0003] At present, the dispersion methods of carbon fiber are divided into physical modification and chemical modification. Physical modification includes ultrasonic dispersion, addition of dispersants, etc. (such as the methods disclosed in Chinese patent applications CN117661374A and CN113293640A); chemical modification includes polydopamine modification, adipic acid modification, etc. However, these methods are generally cumbersome, the cost of chemical synthesis is high, and the chemical treatment has a certain damage effect on the carbon fiber, affecting the performance of the carbon fiber.
[0004] In addition, the fiber used in the prior art has general temperature resistance and is mostly used in the field of low-temperature heating. The general working temperature is below 80°C, which cannot meet the needs of the field of high-temperature heating.
[0005] Therefore, it is of great value to develop a heating paper with uniform heating, high heating efficiency and can be used in high-temperature heating fields and a preparation method thereof. Summary of the invention
[0006] The present invention aims to solve the problems existing in the prior art and provides an aramid-based heating paper and a preparation method thereof. In the preparation method, carbon fibers can be well dispersed, and the prepared aramid-based heating paper has higher uniformity, better mechanical properties and heating properties. At the same time, the aramid-based heating paper has good temperature resistance and can be used in the field of high-temperature heating.
[0007] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing aramid-based heating paper, the preparation method comprising: S1. Preparation of nanofiber dispersion: Adding para-aramid chopped fibers and potassium hydroxide into dimethyl sulfoxide, then adding water, stirring and dispersing, to obtain the nanofiber dispersion; S2. Preparation of chopped fiber dispersion and meta-aramid fiber precipitation: Adding carbon fibers and aramid chopped fibers into the nanofiber dispersion to disperse and mix them evenly to obtain the chopped fiber dispersion; The meta-aramid polymer solution, nanofiber dispersion solution and precipitating agent are continuously and stably added into the precipitation device, and the precipitated fibers are obtained by high-speed shearing, and then cooled and formed in a washing tank, and multi-stage washing is performed to obtain the meta-aramid precipitated fibers; S3. Preparation of aramid-based heating paper: The chopped fiber dispersion and meta-aramid fiber precipitation are subjected to decomposition, stirring, wet forming, pressing, drying and hot pressing to obtain aramid-based heating paper.
[0008] Furthermore, in step S1, the stirring time is 4 to 24 hours, and the storage temperature of the nanofiber dispersion is 15 to 25°C.
[0009] Furthermore, the weight ratio of para-aramid fiber, dimethyl sulfoxide, water and potassium hydroxide is (0.05-3): (80-100): (0.01-0.08): (0.15-4).
[0010] Furthermore, in step S2, when preparing the chopped fiber dispersion, the aramid chopped fibers are para-aramid chopped fibers or meta-aramid chopped fibers, and the deflashing time is 5 to 10 minutes; The mass concentration of the aramid chopped fibers in the chopped fiber dispersion is 0.05% to 1%, and the mass concentration of the carbon fibers in the chopped fiber dispersion is 0.01% to 0.5%.
[0011] Furthermore, in step S2, when preparing the meta-aramid fiber, the meta-aramid polymer solution has a temperature of 35 to 50° C., a solid content of 8% to 15%, and a viscosity of 100 to 450 Po at 25° C.; When preparing the meta-aramid fiber precipitation, the weight ratio of the nanofiber dispersion liquid, the precipitating agent and the meta-aramid polymer liquid is (5-20): (5-12): (80-100).
[0012] Furthermore, in step S2, when preparing the meta-aramid fibrid, the high-speed shearing speed is 3500 to 6000 rpm, and the high-speed shearing time is 40 to 90 s.
[0013] Furthermore, in step S2, when preparing the meta-aramid fiber, the precipitating agent is prepared by mixing and compounding the following materials in parts by weight: 5 to 18 parts of chloride salt, 40 to 50 parts of water, and 40 to 50 parts of N,N-dimethylacetamide; The chloride salt is at least one of lithium chloride, calcium chloride and magnesium chloride.
[0014] Furthermore, in step S3, the weight ratio of the chopped fibers to the meta-aramid fibrids in the chopped fiber dispersion is 5:5, and the carbon fibers in the chopped fiber dispersion account for 10% to 30% of the total weight of the chopped fibers.
[0015] Furthermore, in step S3, the hot pressing conditions are: temperature 180-220° C., vehicle speed 5-20 m / min, and pressure 100-300 N / mm.
[0016] Aramid-based heating paper is prepared according to the preparation method of the present invention, and the aramid-based heating paper can be applied to the field of high-temperature heating.
[0017] The beneficial effects of the present invention are: 1. The nanofiber dispersion is an anionic system, which is very stable and has a certain viscosity. The system can disperse the aramid chopped fibers and carbon fibers and maintain a certain steady state. In the absence of a dispersant, the aramid chopped fibers and carbon fibers can be well dispersed and are not prone to flocculation. The aramid-based heating paper prepared in this way has higher uniformity and better mechanical properties. The carbon fibers in the aramid-based heating paper are more evenly dispersed, which also makes the conductive network more uniform, the heating efficiency higher, and the heating more uniform.
[0018] 2. Aramid fiber is a high-performance fiber material with high strength, high modulus, light weight, folding resistance, high temperature resistance, flame retardancy and corrosion resistance, but it has the characteristics of poor thermal conductivity, easy flocculation and difficult dispersion; carbon fiber has high strength, high modulus, corrosion resistance and good thermal stability, but it has the disadvantages of low elongation at break, poor bonding between fibers during compounding, and easy brittle failure. In the process of precipitation of the nanofiber dispersion in water in the present invention, para-aramid nanofibers are attached to the surface of aramid chopped fibers and carbon fibers, making the smooth surface of aramid chopped fibers and carbon fibers rough. Therefore, this enhances the interfacial bonding strength between fibers, and increases the bonding force between fibers, so that stress is better transferred, the bonding force of aramid-based heating paper is improved, and the problem of low tensile strength and high brittleness of aramid-based heating paper is avoided. At the same time, the present invention does not sacrifice the original mechanical properties of aramid chopped fibers and carbon fibers, and brings the performance of both into better play. In addition, the method can greatly reduce the porosity of aramid-based heating paper, improve the bonding density, and thus improve the overall performance of aramid-based heating paper.
[0019] 3. The introduction of para-aramid nanofibers during the preparation of meta-aramid precipitation reduces the crystallinity of meta-aramid precipitation fibers, making them easier to melt during hot pressing, with stronger bonding between fibers and smoother surfaces. At the same time, the density of aramid-based heating paper is increased, the porosity of aramid-based heating paper is reduced, a more complete conductive path is formed, resistance is reduced, and heating power is increased.
[0020] 4. Compared with conventional meta-aramid fiber precipitation, the low crystallinity meta-aramid fiber precipitation of the present invention can achieve good melting and bonding at a relatively low hot pressing temperature, which can significantly reduce production energy consumption while maintaining the good mechanical properties of aramid-based heating paper. The preparation process of the present invention is simple, energy-saving and easy to control. DETAILED DESCRIPTION
[0021] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.
[0023] A method for preparing aramid-based heating paper, the preparation method comprising: S1. Preparation of nanofiber dispersion: Adding para-aramid chopped fibers and potassium hydroxide into dimethyl sulfoxide, then adding water, and mechanically stirring to obtain the nanofiber dispersion; S2. Preparation of chopped fiber dispersion and meta-aramid fiber precipitation: Adding carbon fibers and aramid chopped fibers into the nanofiber dispersion to disperse and mix them evenly to obtain the chopped fiber dispersion; The meta-aramid polymer solution, nanofiber dispersion and precipitating agent are continuously and stably added to the precipitation device, and the precipitated fibers are sheared at high speed by the precipitation device, and then discharged into the washing tank for further cooling and forming. The cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, thereby obtaining meta-aramid fibrils with low crystallinity; S3. Preparation of aramid-based heating paper: The chopped fiber dispersion and meta-aramid fiber precipitation are subjected to decomposition, stirring, wet forming, pressing, drying and hot pressing to obtain aramid-based heating paper.
[0024] Specifically, in step S1, the stirring time is 4 to 24 hours, and the storage temperature of the nanofiber dispersion is 15 to 25°C.
[0025] Specifically, the weight ratio of para-aramid fiber, dimethyl sulfoxide, water and potassium hydroxide is (0.05-3): (80-100): (0.01-0.08): (0.15-4).
[0026] Specifically, in step S2, when preparing the chopped fiber dispersion, the aramid chopped fibers are para-aramid chopped fibers or meta-aramid chopped fibers, and the deflashing time is 5 to 10 minutes; The mass concentration of the aramid chopped fibers in the chopped fiber dispersion is 0.05% to 1%, and the mass concentration of the carbon fibers in the chopped fiber dispersion is 0.01% to 0.5%.
[0027] Specifically, in step S2, when preparing the meta-aramid fiber, the meta-aramid polymerization liquid has a temperature of 35 to 50° C., a solid content of 8% to 15%, and a viscosity of 100 to 450 Po at 25° C.; When preparing the meta-aramid fiber precipitation, the weight ratio of the nanofiber dispersion liquid, the precipitating agent and the meta-aramid polymer liquid is (5-20): (5-12): (80-100).
[0028] Specifically, in step S2, when preparing the meta-aramid fibrid, the speed of the high-speed shearing is 3500-6000 rpm, and the time of the high-speed shearing is 40-90 s.
[0029] Specifically, in step S2, when preparing the meta-aramid fiber, the precipitating agent is prepared by mixing and compounding the following materials in parts by weight: 5 to 18 parts of chloride salt, 40 to 50 parts of water, and 40 to 50 parts of N,N-dimethylacetamide; The chloride salt is at least one of lithium chloride, calcium chloride and magnesium chloride.
[0030] More specifically, the storage temperature of the precipitating agent is 4-20°C.
[0031] Specifically, in step S3, the weight ratio of the chopped fibers to the meta-aramid fibrids in the chopped fiber dispersion is 5:5, and the carbon fibers in the chopped fiber dispersion account for 10% to 30% of the total weight of the chopped fibers.
[0032] Specifically, in step S3, the hot pressing conditions are: temperature 180-220° C., vehicle speed 5-20 m / min, and pressure 100-300 N / mm.
[0033] More specifically, the para-aramid chopped fibers and meta-aramid chopped fibers used in the embodiments of the present invention are produced by Taihe New Materials Group Co., Ltd., with a length of 4 to 8 mm and a fineness of 1.5 dtex to 2.0 dtex; the carbon fibers used in the embodiments of the present invention have a length of 3 mm to 6 mm and a diameter of 5 to 7 μm. The solvents in the meta-aramid polymer solution used in the embodiments of the present invention are all N,N-dimethylacetamide.
[0034] Aramid-based heating paper is prepared according to the preparation method of the present invention.
[0035] Example 1 Preparation of aramid-based heating paper S1. Preparation of nanofiber dispersion Add para-aramid chopped fibers and potassium hydroxide into dimethyl sulfoxide, then add water, and mechanically stir for 10 hours to obtain a stable nanofiber dispersion; wherein the weight ratio of para-aramid fiber, dimethyl sulfoxide, water and potassium hydroxide is 2:85:0.04:3; and the storage temperature condition of the nanofiber dispersion is 20°C.
[0036] S2. Preparation of aramid chopped fiber dispersion and meta-aramid fiber precipitation (1) Preparation of chopped fiber dispersion Carbon fiber and para-aramid chopped fibers are added into the nanofiber dispersion for decomposition, and after decomposition for 8 minutes, the chopped fiber dispersion is obtained by stirring evenly; wherein the mass concentration of para-aramid chopped fibers in the chopped fiber dispersion is 0.5%, and the mass concentration of carbon fiber in the chopped fiber dispersion is 0.2%.
[0037] (2) Preparation of meta-aramid fiber The meta-aramid polymer solution, the nanofiber dispersion solution and the precipitating agent are continuously and stably added into the precipitation device, and the precipitated fibers are obtained by high-speed shearing at 5000 rpm for 50 seconds in the precipitation device, and then discharged into a washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrils with lower crystallinity; The weight ratio of the nanofiber dispersion, the precipitating agent, and the meta-aramid polymer solution is 10:15:90; The temperature of the meta-aramid polymer solution is 35°C, the solid content is 10%, and the viscosity at 25°C is 195Po; In terms of weight, the precipitating agent is composed of: 10 parts of calcium chloride, 45 parts of water, and 45 parts of N,N-dimethylacetamide.
[0038] S3. Preparation of aramid-based heating paper The chopped fiber dispersion and meta-aramid fiber precipitation are decomposed, stirred, wet-formed, pressed, dried and hot-pressed to obtain aramid-based heating paper; The weight ratio of the chopped fibers to the meta-aramid fibrids in the chopped fiber dispersion is 5:5, and the carbon fibers in the chopped fiber dispersion account for 10% of the total weight of the chopped fibers.
[0039] The hot pressing conditions were: temperature 200 °C, speed 10 m / min, and pressure 150 N / mm.
[0040] Example 2 Preparation of aramid-based heating paper S1. Preparation of nanofiber dispersion Add para-aramid chopped fibers and potassium hydroxide to dimethyl sulfoxide, then add water, and mechanically stir for 24 hours to obtain a stable nanofiber dispersion; wherein the weight ratio of para-aramid fiber, dimethyl sulfoxide, water and potassium hydroxide is 0.15:80:0.01:0.15; and the storage temperature condition of the nanofiber dispersion is 15°C.
[0041] S2. Preparation of aramid chopped fiber dispersion and meta-aramid fiber precipitation: (1) Preparation of chopped fiber dispersion Carbon fiber and para-aramid chopped fibers are added into the nanofiber dispersion for decomposition, and after decomposition for 5 minutes, the chopped fiber dispersion is obtained by stirring evenly; wherein the mass concentration of para-aramid chopped fibers in the chopped fiber dispersion is 0.05%, and the mass concentration of carbon fiber in the chopped fiber dispersion is 0.01%.
[0042] (2) Preparation of meta-aramid fiber The meta-aramid polymer solution, nanofiber dispersion and precipitant are continuously and stably added into a precipitation device, and the precipitated fibers are obtained by high-speed shearing at 6000 rpm for 40 seconds in the precipitation device, and then discharged into a washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrils with lower crystallinity; The weight ratio of the nanofiber dispersion, the precipitating agent, and the meta-aramid polymer solution is 20:12:100; The temperature of the meta-aramid polymer solution is 40°C, the solid content is 8%, and the viscosity is 100Po at 25°C; In terms of weight, the precipitating agent is composed of 5 parts of lithium chloride, 45 parts of water, and 50 parts of N,N-dimethylacetamide.
[0043] S3. Preparation of aramid-based heating paper The chopped fiber dispersion and meta-aramid fiber precipitation are decomposed, stirred, wet-formed, pressed, dried and hot-pressed to obtain aramid-based heating paper; The weight ratio of the chopped fibers to the meta-aramid fibrids in the chopped fiber dispersion is 5:5, and the carbon fibers in the chopped fiber dispersion account for 15% of the total weight of the chopped fibers.
[0044] The hot pressing conditions were: temperature 180 °C, speed 5 m / min, and pressure 100 N / mm.
[0045] Example 3 Preparation of aramid-based heating paper: S1. Preparation of nanofiber dispersion Add para-aramid chopped fibers and potassium hydroxide to dimethyl sulfoxide, then add water, and mechanically stir for 4 hours to obtain a stable nanofiber dispersion; wherein the weight ratio of para-aramid fiber, dimethyl sulfoxide, water and potassium hydroxide is 3:100:0.07:4; the storage temperature condition of the nanofiber dispersion is 25°C.
[0046] S2. Preparation of aramid chopped fiber dispersion and meta-aramid fiber precipitation (1) Preparation of chopped fiber dispersion Carbon fibers and meta-aramid chopped fibers are added into a nanofiber dispersion for decomposition. After decomposition for 10 minutes, the chopped fiber dispersion is obtained by stirring evenly. The mass concentration of the meta-aramid chopped fibers in the chopped fiber dispersion is 1%, and the mass concentration of the carbon fibers in the chopped fiber dispersion is 0.5%.
[0047] (2) Preparation of meta-aramid fiber The meta-aramid polymer solution, nanofiber dispersion and precipitant are continuously and stably added into a precipitation device, and the precipitated fibers are obtained by high-speed shearing at 3500 rpm for 90 seconds in the precipitation device, and then discharged into a washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrils with lower crystallinity; The weight ratio of the nanofiber dispersion, the precipitating agent, and the meta-aramid polymer solution is 5:5:90; The temperature of the meta-aramid polymer solution is 50°C, the solid content is 15%, and the viscosity is 450Po at 25°C; In terms of weight, the precipitating agent is composed of: 18 parts of magnesium chloride, 40 parts of water, and 42 parts of N,N-dimethylacetamide.
[0048] S3. Preparation of aramid-based heating paper The chopped fiber dispersion and meta-aramid fiber precipitation are decomposed, stirred, wet-formed, pressed, dried and hot-pressed to obtain aramid-based heating paper; The weight ratio of the chopped fibers to the meta-aramid fibrids in the chopped fiber dispersion is 5:5, and the carbon fibers in the chopped fiber dispersion account for 25% of the total weight of the chopped fibers.
[0049] The hot pressing conditions were: temperature 220 °C, speed 20 m / min, and pressure 300 N / mm.
[0050] Example 4 Preparation of aramid-based heating paper S1. Preparation of nanofiber dispersion Add para-aramid chopped fibers and potassium hydroxide to dimethyl sulfoxide, then add water, and mechanically stir for 16 hours to obtain a stable nanofiber dispersion; wherein the weight ratio of para-aramid fiber, dimethyl sulfoxide, water and potassium hydroxide is 0.05:85:0.08:2; and the storage temperature condition of the nanofiber dispersion is 25°C.
[0051] S2. Preparation of chopped fiber dispersion and meta-aramid fiber precipitation (1) Preparation of chopped fiber dispersion Carbon fiber and meta-aramid chopped fibers are added into the nanofiber dispersion for decomposition, and after decomposition for 6 minutes, the chopped fiber dispersion is obtained by stirring evenly; wherein the mass concentration of the meta-aramid chopped fibers in the chopped fiber dispersion is 0.6%, and the mass concentration of the carbon fiber in the chopped fiber dispersion is 0.3%.
[0052] (2) Preparation of meta-aramid fiber The meta-aramid polymer solution, the nanofiber dispersion solution and the precipitating agent are continuously and stably added into the precipitation device, and the precipitated fibers are obtained by high-speed shearing at 5000 rpm for 50 seconds in the precipitation device, and then discharged into a washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrils with lower crystallinity; The weight ratio of the nanofiber dispersion, the precipitating agent, and the meta-aramid polymer solution is 10:10:80; The temperature of the meta-aramid polymer solution is 35°C, the solid content is 12%, and the viscosity is 300Po at 25°C; In terms of weight, the precipitating agent is composed of: 15 parts of calcium chloride, 43 parts of water, and 42 parts of N,N-dimethylacetamide.
[0053] S3. Preparation of aramid-based heating paper The chopped fiber dispersion and meta-aramid fiber precipitation are decomposed, stirred, wet-formed, pressed, dried and hot-pressed to obtain aramid-based heating paper; The weight ratio of the chopped fibers to the meta-aramid fibrids in the chopped fiber dispersion is 5:5, and the carbon fibers in the chopped fiber dispersion account for 30% of the total weight of the chopped fibers.
[0054] The hot pressing conditions were: temperature 190 °C, speed 10 m / min, and pressure 180 N / mm.
[0055] Comparative Example 1 The aramid-based heating paper was prepared by the same method as in Example 1, except that in step S1, the storage temperature of the nanofiber dispersion was increased. In this comparative example 1, the storage temperature of the nanofiber dispersion was 35°C.
[0056] Comparative Example 2 The aramid-based heating paper was prepared by the same method as in Example 1, except that in step S1, the storage temperature of the nanofiber dispersion was lowered. In this comparative example 2, the storage temperature of the nanofiber dispersion was 5°C.
[0057] Comparative Example 3 The aramid-based heating paper is prepared by the same method as in Example 1, except that in step S2, when preparing meta-aramid fiber precipitation, the dosage ratio of the nanofiber dispersion is increased. In this comparative example 3, the weight ratio of the nanofiber dispersion, the precipitating agent, and the meta-aramid polymerization liquid is 25:10:90.
[0058] Comparative Example 4 The aramid-based heating paper is prepared by the same method as in Example 1, except that in step S2, when preparing meta-aramid fiber precipitation, the dosage ratio of the nanofiber dispersion is reduced. In this comparative example 4, the weight ratio of the nanofiber dispersion, the precipitating agent, and the meta-aramid polymerization liquid is 1:10:90.
[0059] Comparative Example 5 The aramid-based heating paper was prepared by the same method as in Example 1, except that in step S2, when preparing meta-aramid fiber, the shear rate was increased. In this comparative example 5, the shear rate of step S2 was 8000 rpm.
[0060] Comparative Example 6 The aramid-based heating paper was prepared by the same method as in Example 1, except that in step S2, when preparing meta-aramid fibrillation, the shear rate was reduced. In this comparative example 6, the shear rate of step S2 was 2000 rpm.
[0061] Comparative Example 7 The conventional method is to coat the nanofiber dispersion on the surface of the aramid-based heating paper. The specific preparation process is as follows: S1. Preparation of nanofiber dispersion: The nanofiber dispersion was prepared by the same method as in Example 1; S2. Preparation of chopped fiber dispersion and meta-aramid fiber precipitation (1) Preparation of chopped fiber dispersion The steps are the same as those in Example 1, except that no nanofiber dispersion is used in the preparation of the chopped fiber dispersion.
[0062] The carbon fiber and para-aramid chopped fibers are added into a proper amount of water for disintegration, and after disintegration for 8 minutes, the chopped fiber dispersion is obtained by stirring evenly; wherein the mass concentration of the para-aramid chopped fibers in the chopped fiber dispersion is 0.5%, and the mass concentration of the carbon fiber in the chopped fiber dispersion is 0.2%.
[0063] (2) Preparation of meta-aramid fiber The preparation steps are the same as those in Example 1, except that no nanofiber solution is added during the preparation of meta-aramid fibrids. The specific steps are as follows: The meta-aramid polymer solution and the precipitating agent are continuously and stably introduced into the precipitating device, and the precipitated fibers are obtained by high-speed shearing at 5000 rpm for 50 seconds in the precipitating device, and then discharged into a water washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrids; The weight ratio of the precipitating agent to the meta-aramid polymer solution is 15:90; The temperature of the meta-aramid polymer solution is 35°C, the solid content is 10%, and the viscosity at 25°C is 195Po; In terms of weight, the precipitating agent is composed of: 10 parts of calcium chloride, 45 parts of water, and 45 parts of N,N-dimethylacetamide.
[0064] S3. Preparation of aramid-based heating paper Aramid short fiber dispersion and meta-aramid fiber precipitation are decomposed, stirred, wet-formed, pressed and dried to obtain aramid-based heating paper; The weight ratio of the chopped fibers to the meta-aramid fibrids in the chopped fiber dispersion is 5:5, and the carbon fibers in the chopped fiber dispersion account for 8% of the total weight of the chopped fibers.
[0065] S4. Coating of Nanofiber Dispersion The nanofiber dispersion prepared in step S1 is uniformly coated on one side of the aramid-based heating paper prepared in step S3, and then washed and dried. Then, the above steps are repeated on the other side of the aramid-based heating paper to control the total coating amount of the nanofibers on the aramid-based heating paper to be 2 g / m 2 Finally, the aramid-based heating paper coated with nanofibers on both sides was hot-pressed to obtain the final product. The hot-pressing conditions were: temperature 200°C, vehicle speed 10m / min, and pressure 150N / mm.
[0066] Comparative Example 8 The aramid-based heating paper was prepared by the same method as in Example 1, except that the conventional method was used to prepare the chopped fiber dispersion and the meta-aramid fibrid. That is, in this comparative example 8, no nanofiber dispersion was used when preparing the chopped fiber dispersion, and no nanofiber solution was added during the preparation of the meta-aramid fibrid.
[0067] The preparation process of the chopped fiber dispersion and meta-aramid fiber precipitate in this comparative example is as follows: (1) Preparation of chopped fiber dispersion The carbon fiber and para-aramid chopped fibers are added into a proper amount of water for disintegration, and after disintegration for 8 minutes, the chopped fiber dispersion is obtained by stirring evenly; wherein the mass concentration of the para-aramid chopped fibers in the chopped fiber dispersion is 0.5%, and the mass concentration of the carbon fiber in the chopped fiber dispersion is 0.2%.
[0068] (2) Preparation of meta-aramid fiber The meta-aramid polymer solution and the precipitating agent are continuously and stably introduced into the precipitating device, and the precipitated fibers are obtained by high-speed shearing at 5000 rpm for 50 seconds in the precipitating device, and then discharged into a water washing tank for further cooling and forming, and the cooled and formed precipitated fiber mixture containing N,N-dimethylacetamide solvent is subjected to multi-stage water washing to remove the N,N-dimethylacetamide solvent, so as to obtain meta-aramid fibrids; The weight ratio of the precipitating agent to the meta-aramid polymer solution is 15:90; The temperature of the meta-aramid polymer solution is 35°C, the solid content is 10%, and the viscosity at 25°C is 195Po; In terms of weight, the precipitating agent is composed of: 10 parts of calcium chloride, 45 parts of water, and 45 parts of N,N-dimethylacetamide.
[0069] Comparative Example 9 The aramid-based heating paper was prepared by the same method as in Example 1, except that the conventional method was used to prepare the chopped fiber dispersion, that is, the nanofiber dispersion was not used in the preparation of the chopped fiber dispersion in this comparative example 9. The specific preparation process of the chopped fiber dispersion in this comparative example 9 is as follows: The carbon fiber and para-aramid chopped fibers are added into a proper amount of water for disintegration, and after disintegration for 8 minutes, the chopped fiber dispersion is obtained by stirring evenly; wherein the mass concentration of the para-aramid chopped fibers in the chopped fiber dispersion is 0.5%, and the mass concentration of the carbon fiber in the chopped fiber dispersion is 0.2%.
[0070] Comparative Example 10 The aramid-based heating paper was prepared by the same method as in Example 1, except that the conventional method was used to prepare the meta-aramid fibrils, that is, no nanofiber dispersion was used when preparing the meta-aramid fibrils in this comparative example 10, and the preparation process of the meta-aramid fibrils in this comparative example 10 was the same as the preparation method of the meta-aramid fibrils in comparative example 8.
[0071] The aramid-based heating papers prepared in the above examples and comparative examples were subjected to performance tests, and the test methods involved are specifically as follows.
[0072] The quantitative test method refers to the standard GB / T 451.2; The thickness test method refers to GB / T 451.3; The reference standard for tensile strength and elongation test methods is GB / T 12914; The tear strength test method refers to GB / T 455; The heating technical indicators refer to the standard GB / T4564; the radiation surface electric-thermal radiation conversion rate refers to the proportion of the electrical energy consumed by the carbon fiber paper when it is powered on and heated, which is converted into thermal radiation energy. The higher the proportion, the higher the heating efficiency of the product.
[0073] The specific test results are shown in Table 1.
[0074] Table 1 Aramid-based heating paper performance test data
[0075] From the above table data, it can be seen that the aramid-based heating paper prepared by the preparation method of the present invention in Examples 1 to 4 has good uniformity, excellent mechanical properties and heating properties. In addition, the aramid-based heating paper prepared by the preparation method of the present invention in Examples 1 to 4 has a very high conversion rate of electric heat radiation, and the temperature of the radiation surface is very uniform.
[0076] In Examples 1-4 of the present invention, the carbon fiber and aramid short fibers are well dispersed in the nano-dispersion liquid, so that the overall performance of the aramid-based heating paper is significantly improved. At the same time, the aramid nanofibers adhered to the surface of the carbon fiber and aramid short fibers act as a binder, which not only fills the pores of the aramid-based heating paper, but also strengthens the interaction with other fibers, and well avoids the problems of low mechanical properties and large brittleness caused by the poor bonding between aramid fibers and carbon fibers. In addition, the nanofiber dispersion is introduced during the preparation of meta-aramid fiber precipitation, so that its crystallinity is moderately reduced, meeting the balance between energy saving and excellent performance in the processing process. Compared with conventional meta-aramid fiber precipitation, the meta-aramid fiber precipitation surface prepared by the present invention has more tiny wrinkles, which can be more strongly bonded to other fibers. At the same time, a strong hydrogen bond force can be formed between the nanofibers and the carbon fiber, aramid short chopped or meta-aramid fiber precipitation. Under multiple effects, the aramid-based heating paper in the present invention has excellent overall performance.
[0077] From the data comparison of Comparative Example 1, Comparative Example 2 and Example 1, it can be seen that if the storage temperature of the nano-dispersion liquid is increased or decreased, the mechanical properties, uniformity, electrothermal radiation conversion rate and other indicators of the aramid-based heating paper will be significantly reduced. This is because the nano-dispersion liquid is at a suitable temperature, the carbon fiber and aramid short fibers will be dispersed more evenly, the prepared meta-aramid fiber will be more uniform in size, and maintain a suitable crystallinity and microscopic morphology (i.e., the surface has more tiny wrinkles). Therefore, the overall performance of the aramid-based heating paper finally prepared is significantly improved.
[0078] From the data comparison of Comparative Examples 3, 4 and Example 1, it can be seen that if the proportion of nanofibers is increased or decreased, the overall performance of the aramid-based heating paper will also be significantly reduced. This is because by selecting a suitable nanofiber ratio, the prepared meta-aramid fibrils will be more uniform in size and maintain a suitable crystallinity and microscopic morphology, and the prepared aramid-based heating paper will have better uniformity, and the mechanical properties and heating properties will be better. At the same time, by selecting a suitable nanofiber ratio, the dispersion state of carbon fiber and aramid chopped fiber will reach the best, and the aramid-based heating paper will be given good mechanical properties, uniformity and heating properties.
[0079] From the data comparison of Comparative Examples 5, 6 and Example 1, it can be seen that the overall performance of aramid-based heating paper is better when the appropriate shear rate is maintained. When the shear rate is too high, the length of the meta-aramid fibrils will be shortened, and the film characteristics of the meta-aramid fibrils will also decrease accordingly, which will cause the contact area between the meta-aramid fibrils and the carbon fibers or aramid short fibers to decrease, resulting in a decrease in the mechanical properties and heating properties of the paper. When the shear rate is too low, the shear force on the aramid droplets is insufficient, and the aramid droplets dispersed in the precipitant are large and cannot be fully stretched into a film state, thereby causing the overall performance of the aramid-based heating paper to decrease. In addition, maintaining a certain shear rate is crucial for the crystallinity of the meta-aramid fibrils. When the shear rate is too high, the aramid droplets are under the action of high-speed shear, and the fibers are easy to present a film state, the crystalline structure is destroyed, resulting in a low crystallinity, thereby reducing the fiber strength, and further reducing the mechanical properties of the aramid-based heating paper. On the contrary, if the shear rate is too low, the crystallinity of the meta-aramid fibrils will be too high, which will cause the polymer chain segments to be over-aggregated, reduce the gaps, reduce the flexibility of the molecular chain, and thus reduce the mechanical properties of the paper. The present invention controls the conditions so that the crystallinity of the prepared meta-aramid fibrils is moderately reduced compared to the traditional meta-aramid fibrils, which can not only save energy consumption in the hot pressing process, but also significantly improve the overall performance of the aramid-based heating paper.
[0080] From the comparison of the data of Comparative Example 7 and Example 1, it can be seen that compared with the method of coating nanofibers on the surface of aramid-based heating paper, the aramid-based heating paper in the present invention has better overall performance.
[0081] From the comparison of the data of Comparative Example 8 and Example 1, it can be seen that compared with the conventional preparation method of aramid-based heating paper, the aramid-based heating paper prepared by the present invention has significant improvements in mechanical properties, uniformity and heating performance.
[0082] From the comparison of the data of Comparative Examples 9, 10 and Example 1, it can be seen that the aramid-based heating paper prepared by using both the meta-aramid fibrid and the meta-aramid chopped fiber dispersion of the present invention has better overall performance.
[0083] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0084] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.
Claims
1. A method for preparing aramid-based heating paper, characterized in that: The preparation method is: S1. Preparation of nanofiber dispersion: Adding para-aramid chopped fibers and potassium hydroxide into dimethyl sulfoxide, then adding water, stirring and dispersing, to obtain the nanofiber dispersion; S2. Preparation of chopped fiber dispersion and meta-aramid fiber precipitation: Adding carbon fibers and aramid chopped fibers into the nanofiber dispersion to disperse and mix them evenly to obtain the chopped fiber dispersion; The meta-aramid polymer solution, nanofiber dispersion solution and precipitating agent are continuously and stably added into the precipitation device, and the precipitated fibers are obtained by high-speed shearing, and then cooled and formed in a washing tank, and multi-stage washing is performed to obtain the meta-aramid precipitated fibers; S3. Preparation of aramid-based heating paper: The chopped fiber dispersion and meta-aramid fiber precipitation are subjected to decomposition, stirring, wet forming, pressing, drying and hot pressing to obtain aramid-based heating paper.
2. The method for preparing an aramid-based heating paper according to claim 1, characterized in that: In step S1, the stirring time is 4 to 24 hours, and the storage temperature of the nanofiber dispersion is 15 to 25°C.
3. The method for preparing an aramid-based heating paper according to claim 1, characterized in that: The weight ratio of para-aramid fiber, dimethyl sulfoxide, water and potassium hydroxide is (0.05-3): (80-100): (0.01-0.08): (0.15-4).
4. The method for preparing an aramid-based heating paper according to claim 1, characterized in that: In step S2, when preparing the chopped fiber dispersion, the aramid chopped fibers are para-aramid chopped fibers or meta-aramid chopped fibers, and the deflashing time is 5 to 10 minutes; The mass concentration of the aramid chopped fibers in the chopped fiber dispersion is 0.05% to 1%, and the mass concentration of the carbon fibers in the chopped fiber dispersion is 0.01% to 0.5%.
5. The method for preparing an aramid-based heating paper according to claim 1, characterized in that: In step S2, when preparing the meta-aramid fibrid, the meta-aramid polymer solution has a temperature of 35 to 50° C., a solid content of 8% to 15%, and a viscosity of 100 to 450 Po at 25° C.; When preparing the meta-aramid fiber precipitation, the weight ratio of the nanofiber dispersion liquid, the precipitating agent and the meta-aramid polymer liquid is (5-20): (5-12): (80-100).
6. The method for preparing an aramid-based heating paper according to claim 1, characterized in that: In step S2, when preparing the meta-aramid fibrid, the speed of the high-speed shearing is 3500-6000 rpm, and the time of the high-speed shearing is 40-90 s.
7. The method for preparing an aramid-based heating paper according to claim 1, characterized in that: In step S2, when preparing the meta-aramid fiber, the precipitating agent is prepared by mixing the following materials in parts by weight: 5 to 18 parts of chloride salt, 40 to 50 parts of water, and 40 to 50 parts of N,N-dimethylacetamide; The chloride salt is at least one of lithium chloride, calcium chloride and magnesium chloride.
8. The method for preparing an aramid-based heating paper according to claim 1, characterized in that: In step S3, the weight ratio of the chopped fibers to the meta-aramid fibrids in the chopped fiber dispersion is 5:5, and the carbon fibers in the chopped fiber dispersion account for 10% to 30% of the total weight of the chopped fibers.
9. The method for preparing an aramid-based heating paper according to claim 1, characterized in that: In step S3, the hot pressing conditions are: temperature 180-220° C., vehicle speed 5-20 m / min, and pressure 100-300 N / mm.
10. A kind of aramid-based heating paper, characterized in that: The aramid-based heating paper is prepared according to the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method and application of high-adhesion carbon paper for fuel cell
CN117661374A
Electrothermal high-temperature-resistant carbon fiber paper and preparation method thereof
CN103451989A
Novel carbon fiber heating paper manufacturing method
CN109098029A
Para-position nanometer aramid fiber and carbon nano-tube composite paper preparation method
CN110846926A
High-conductivity aramid insulation paper-based material for large oil-immersed transformer and preparation method of high-conductivity aramid insulation paper-based material
CN112681010A